DAMPAK PERUBAHAN BUDAYA DI KOTA BAUBAU TERHADAP PEMBELAJARAN DI SEKOLAH DASAR - Delia Dafista Zida; Annadwi Usman; Haliadi (CV. Adiba Aisha Amira, 2026)
The cultural changes occurring in Baubau City are the impact of globalization, the development of information technology, and the increasing interaction of society with foreign cultures. These changes bring significant implications for the field of education, particularly in the learning process at elementary schools, which play an important role in shaping students' character. This study aims to analyze the impact of cultural changes on learning in elementary schools in Baubau City, both in terms of student behavior, character values, and teachers' learning strategies. The research problem focuses on the shift in local cultural values and its influence on students' attitudes, learning habits, and social interactions within the school environment. The research method used is qualitative research with a descriptive approach. Data collection is conducted through classroom observation, interviews with teachers and school principals, as well as documentation studies of learning tools..